PENGGUNAAN KOMPOS TANDAN KOSONG KELAPA SAWIT SEBAGAI SUBTITUSI PUPUK NPK DALAM PEMBIBITAN AWAL KELAPA SAWIT - Andi Kurnia Agung; Teguh Adiprasetyo Adiprasetyo; Hermansyah Hermansyah (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2019)
[THE USE OF OIL PALM EMPTY-FRUIT-BUNCHES COMPOST AS THE SUBTITUTE FOR NPK FERTILIZER IN THE OIL PALM PRE-NURSERY]. Compost of oil palm empty fruit bunches (OPEFB) is rich in nutriets needed to support the plant growth and offers as the substitute for chemical fertilizers. The purpose of this study was to determine the rates OPEFB compost and NPK fertilizer applications on the best suited for the growth of oil palm seedlings during pre-nursery. The OPEFB compost at 50, 100, and 150 g/pot was applied in factorial combination with with NPK at 0.0, 2.5, and 5.0 g/pot. Data were collected for seedling height, stem diameter, leaf number and leaves greenness. Higher leaf number was observed when OPEFB compost applied at 100 or 150 g/plot with or without additional NPK. Seedling height, stem diameter, and leaves greenness were increased with the application of OPEFB compost at 50 g/pot but no further increase with the additional rates. Additional application of NPK only increased the leaf greenness.